An Examination of Changes in Residents' Perceptions of Tourism Impacts Over Time: The Impact of Residents' Socio-demographic Characteristics - Sharma, B.; Gursoy, Dogan (Routledge, 2014)
This study investigates whether there has been a change in residents' perceptions of various tourism impacts over time and the impact of residents' socio-demographic characteristics on those changes. A survey of local residents (n = 732 in 2004 and n = 590 in 2009) was carried out for collecting the data for this study which was then followed by focus groups, conducted in 2012, consisting of academics, local residents and the tourism experts to validate the outcome from the survey. The results suggest that there has been significant increase in the level of agreement of the Sunshine Coast residents during this period on some of the tourism impacts such as job creation, attracting more investment, providing more business for local people and more cultural exchange between tourists and residents. The results also suggest that there is a significant decline in their perceptions of tourism negatively affecting the way of living of local residents and likelihood of residents suffering from living in a tourism destination. The residents also feel that there will be a decline in parks and other recreational areas for local residents with growth in tourism. The study also found that demographic variables such as age, gender, income, education and occupation are likely to influence residents' perceptions of tourism impact over time. Implications for future tourism development plans for the region are discussed.